2015
DOI: 10.1245/s10434-015-4414-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma in Asian Populations Over the Age of 40 Years: A Multicenter Study

Abstract: This study revealed distinct clinicopathological features of OSA patients over 40 years of age compared with younger patients, such as the high incidence of axial tumors, common osteolytic and mixed radiographic findings, the high frequency of unusual histologic subtypes, and poor prognosis. Contrary to Western elderly patients with OSA, there was no Paget's OSA in this study, which may result in a lower incidence of secondary OSA. Prognostic factor analyses demonstrated chemotherapy did not influence OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 22 publications
2
34
1
1
Order By: Relevance
“…Thirty‐five studies met the inclusion criteria (Table ): very high HDI (n = 23), high HDI (n = 7), and medium/low HDI (n = 5) . Figure depicts the prevalence of metastatic OS at diagnosis stratified by HDI group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐five studies met the inclusion criteria (Table ): very high HDI (n = 23), high HDI (n = 7), and medium/low HDI (n = 5) . Figure depicts the prevalence of metastatic OS at diagnosis stratified by HDI group.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five studies met the inclusion criteria (Table I): very high HDI (n = 23), [1,6,8,10,[13][14][15][16][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] high HDI (n = 7), [3,11,12,[36][37][38][39] and medium/low HDI (n = 5). [2,[40][41][42][43] Figure 1 depicts the prevalence of metastatic OS at diagnosis stratified by HDI group.…”
Section: Resultsmentioning
confidence: 99%
“…The role of chemotherapy in elderly patients has remained controversial. Several studies have shown that the currently available systemic chemotherapies are not effective in the elderly patients . However, some reports do suggest the benefits of chemotherapy in elderly patients with osteosarcoma .…”
Section: Discussionmentioning
confidence: 99%
“…The differences include a more frequent involvement of the axial bones, a lower tolerance to aggressive chemotherapy, and often secondary to Paget's disease or radiation therapy . Secondary osteosarcoma was reported as accounting for one‐third to one‐half of all elderly patients with osteosarcoma, while the corresponding figures in Asian population has been reported to range from 12.6% to 22% . Elderly patients with primary osteosarcoma tend to respond poorly to chemotherapy .…”
mentioning
confidence: 99%
“…In pediatric patients with localized disease, ~80-90% of 5-year overall survival is achieved when treated at experienced centers (3)(4)(5); however, in adult patients (6,7) and patients with recurrent or metastatic disease (3,8,9), response to chemotherapy is less satisfactory, and survival of such patients is generally poor.…”
Section: Introductionmentioning
confidence: 99%